Možnosti měření, predikace a regulace disperse pachových látek - Svobodová, Zuzana (Univerzita Pardubice, 2003)
The problem of odour air pollution is becoming more relevant in the last time because of the new legislation. For the large numer of subjects the new rights and obligations was set in. Having posibility for sampling, analysing, estimating and controlling of odour annoyance are responsible points of odour impact assesment. In the Czech Republic the odour dispersion research is not so advanced as abroad. Therefore we have started our research in the scope of odour prediciton. Data set obtained by fied survey and dynamic olfaktometry will be useful for determination of any odour dispersion model.
Keywords: pachové látky; Měření; Analýza; regulace